Frequencies of abnormal humoral and cellular immune component levels in peripheral blood of patients with recurrent aphthous ulceration - Huan-Huan Ruan; Guo-Yang Li; Ning Duan; Hong-Liu Jiang; Yi-Fu Fu; Yue-Feng Song; Qian Zhou; Xiang Wang; Wen-Mei Wang (Elsevier, 2018)
Background/purpose: Recurrent aphthous ulceration (RAU) has an incidence of approximately 20% in general population. However, its exact cause remains unknown. Increasing evidence suggests that immunologic mechanisms may play crucial roles in the etiology of this disease. Materials and methods: The peripheral blood samples were obtained from 85 patients with RAU during acute phase and 87 healthy controls. The serum levels of IgG, IgA, IgM, C3 and C4 were measured by immunoturbidimetry. In addition, the serum IgE levels were measured by electro-chemiluminescence immunoassay. Furthermore, the percentages of B, T, CD4+ T, CD8+ T lymphocytes and natural killer (NK) cells in peripheral blood were determined by flow cytometry. Results: Our findings showed that the serum IgG, IgA, IgE, C3 and C4 levels of RAU patients were significantly higher than those of healthy controls. The percentages of CD4+ T cells and B cells in peripheral blood of RAU patients were significantly decreased, whereas the percentages of CD8+ T cells and NK cells of RAU patients were remarkably increased. Our results indicated that the IgG level was elevated in 18 patients (21.2%) and that the IgE level was increased in 21 patients (24.7%). Our results also showed that the frequency of abnormal IgG or IgE levels were significantly correlated with that of abnormal CD8+ T cell percentage in RAU patients. Conclusion: The levels of both humoral and cellular immune components could be altered in RAU. The relationship between humoral and cellular immune may be potentially important immunologic aspects involved in the pathogenesis of RAU.